A presença de Émile Durkheim em Oliveira Vianna : contribuições ao pensamento social e político brasileiro - Fontana, Felipe (2013)
This work has the purpose of presenting the results of the research called The Presence of Émile Durkheim in Oliveira Vianna: Contributions to the Brazilian Social and Political Thought. In this study we found analyzes that seek to establish connections between the thought of Emile Durkheim and the theory of Oliveira Vianna. For this reason, we highlight, through a literature review and a research at the Museum Casa de Oliveira Vianna, a series of conceptual axis and thematic axis that best demonstrate the ties between both authors, they are: the categories of Collective Consciousness, Social Solidarity, Social Morphology and the concepts of State and Corporatism. For the achievement of our research, we elected the Sociology of Knowledge as the source of methodological presuppositions that led our activities. In this way, we do some bibliographic comparisons between the thought of both thinkers. We analyzed the historical contexts of the authors studied and the perception they had of their realities. And we had the opportunity to work on the collection of the fluminense intellectual with the purpose of ascertaining whether the works present there had some connection with durkheimian thought. All these activities were carried out with the purpose of surround us in the maximum of data and facts that show the ties between the intellectuals, enabling us, the interpellation of our initial hypotheses. In general, we note that Oliveira Vianna made a specific use of certain meanings attached to some concepts of Durkheim's thought and employed these meanings in their explanations about Brazil and the formation of the Brazilian nation. The concept of social solidarity, for example, the step that used to explain the lack of cohesion and integration in Brazil Colony reveals, according to our research and interpretation, characteristics of durkheimian definition of this category. In addition, the tags (stress or markings) of Oliveira Vianna geared to this conceptual axis, found by us in the work The Division of Labour in Society and in certain manuals of sociology located in the collection of the niteroinse intellectual, also leads us to perceive a connection between both authors, which is mediated by the concept of Social Solidarity. Finally, we believe that Oliveira Vianna has made a significant use of durkheimian concepts to constitute his theories about the Brazil, thereby revealing, an important presence of the thought of Emile Durkheim in his theory, and was precisely the need to delimit such presence in a profound way that motivated this research.